Efficacy of Visual–Acoustic Biofeedback Intervention for Residual Rhotic Errors: A Single-Subject Randomization Study - McAllister Byun, Tara (Journal of speech, language, and hearing research, 2017)
Purpose: This study documented the efficacy of visual-acoustic biofeedback intervention for residual rhotic errors, relative to a comparison condition involving traditional articulatory treatment. All participants received both treatments in a single-subject experimental design featuring alternating treatments with blocked randomization of sessions to treatment conditions. Method: Seven child and adolescent participants received 20 half-hour sessions of individual treatment over 10 weeks. Within each week, sessions were randomly assigned to feature traditional or biofeedback intervention. Perceptual accuracy of rhotic production was assessed in a blinded, randomized fashion. Each participant's response to the combined treatment package was evaluated by using effect sizes and visual inspection. Differences in the magnitude of response to traditional versus biofeedback intervention were measured with individual randomization tests. Results: Four of 7 participants demonstrated a clinically meaningful response to the combined treatment package. Three of 7 participants showed a statistically significant difference between treatment conditions. In all 3 cases, the magnitude of within-session gains associated with biofeedback exceeded the gains associated with traditional treatment. Conclusions: These results suggest that the inclusion of visual-acoustic biofeedback can enhance the efficacy of intervention for some individuals with residual rhotic errors. Further research is needed to understand which participants represent better or poorer candidates for biofeedback treatment.